2012
DOI: 10.1007/s00125-012-2541-1
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine protein phosphatase 5 regulates glucose homeostasis in vivo and apoptosis signalling in mouse pancreatic islets and clonal MIN6 cells

Abstract: Aims/hypothesis During the development of type 2 diabetes mellitus, beta cells are often exposed to a high glucose/ hyperlipidaemic environment, in which the levels of reactive oxygen species (ROS) are elevated. In turn, ROS can trigger an apoptotic response leading to beta cell death, by activating mitogen-activated protein kinase (MAPK) signalling cascades. Here we test the hypothesis that serine/threonine protein phosphatase 5 (PP5) acts to suppress proapoptotic c-Jun N-terminal kinase (JNK) signalling in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…PP5 may accordingly act as a negative regulator of the ASK1/JNK signaling pathway and in so doing protecting cells from apoptosis (Kutuzov et al 2005; Mkaddem, et al 2009; Morita et al 2001). This concept was supported by the recent publication (Grankvist et al 2012) showing that islets from mice lacking PP5 were more susceptible towards stress-induced apoptosis than wild-type cognates. Additionally, PP5-deficient mice had lower fasting glycemia and improved glucose tolerance compared to the wild-type mice, suggesting a novel role for PP5 in the regulation of glucose homeostasis.…”
Section: Protein Phosphatases In β-Cell Proliferation and Apoptosismentioning
confidence: 77%
See 2 more Smart Citations
“…PP5 may accordingly act as a negative regulator of the ASK1/JNK signaling pathway and in so doing protecting cells from apoptosis (Kutuzov et al 2005; Mkaddem, et al 2009; Morita et al 2001). This concept was supported by the recent publication (Grankvist et al 2012) showing that islets from mice lacking PP5 were more susceptible towards stress-induced apoptosis than wild-type cognates. Additionally, PP5-deficient mice had lower fasting glycemia and improved glucose tolerance compared to the wild-type mice, suggesting a novel role for PP5 in the regulation of glucose homeostasis.…”
Section: Protein Phosphatases In β-Cell Proliferation and Apoptosismentioning
confidence: 77%
“…Additionally, PP5-deficient mice had lower fasting glycemia and improved glucose tolerance compared to the wild-type mice, suggesting a novel role for PP5 in the regulation of glucose homeostasis. These findings cannot be explained by a difference in islet mass between the PP5-deficient and wild-type mice, since no difference was observed (Grankvist et al 2012). Furthermore, a high-fat diet treatment for 10 weeks revealed that the mice lacking PP5 gained markedly less weight, did not accumulate visceral fat and displayed enhanced insulin sensitivity compared to the wild-type littermates (Grankvist et al 2013).…”
Section: Protein Phosphatases In β-Cell Proliferation and Apoptosismentioning
confidence: 96%
See 1 more Smart Citation
“…The decrease of PURA reduces postsynaptic density protein 95 [22], which contributes to neuronal cell loss after status epilepticus [23] and KA administration [24]. PP5, a serine/threonine phosphatase, is widely expressed in brain including hippocampus [25] and suppresses apoptosis by regulating c-Jun N-terminal kinase phosphorylation [26] and apoptosis signal-regulating kinase 1 activity [27]. T-complex protein 1 (TCP-1), a chaperonin family member, that folds protein properly [28], supports the maintenance of the native forms of cytoskeletal proteins [29], and the overexpression of all TCP-1 subunits suppressed Neuro2a cell death induced by the cytotoxicity of polyglutamine-expansion proteins [30].…”
Section: Discussionmentioning
confidence: 99%
“…It could be that other SMAD2/3 interacting partners could be dephosphorylated by PP5. Thirdly, PP5 has been implicated in the regulation of multiple pathways, including adipogenesis by controlling the GRα and PPARγ phosphorylation (34), DNA-damage repair by controlling the ATM/ATR/Chk1 and p53 pathway components (21,31,34-37), MAPK-mediated growth and differentiation (38)(39)(40)(41)(42)(43)(44), and cell cycle arrest (45). Interestingly, GRα has also been implicated in the repression of the TGFβ pathway by its association with SMAD3 (46).…”
Section: Discussionmentioning
confidence: 99%